Teacher man : a memoir - McCourt, Frank (New York : Scribner, 2005)
In this tribute to teachers everywhere. McCourt records the trials, triumphs and surprises he faces in public high schools around New York City. His methods anything but conventional, McCourt creates a lasting impact on his students through imaginative assignments, singalongs and field trips. As he struggles to find his way in the classroom, he spends his evenings drinking with writers and dreaming of one day putting his own story to paper. The book shows McCourt developing his ability to tell a great story as he works to gain the attention and respect of unruly or indifferent adolescents. His rocky marriage, his failed attempt to get a Ph.D. at Trinity College, Dublin, and his repeated firings due to his propensity to talk back to his superiors ironically lead him to New York's most prestigious school, Stuyvesant High School, where he finally finds a place and a voice.--From publisher description.
It's a long road to pedagogy -- Donkey on a thistle -- Coming alive in room 205.
Keywords: McCourt, Frank; High school teachers -- New York (State) -- New York -- Biography; Irish Americans -- Biography